Corporate governance in the European insurance Industry - Ricci, Ornella; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2014)
Corporate Governance in the European Insurance Industry provides a unique perspective on insurance corporate governance and regulation in the context of the recent global financial crisis.
Keywords: Finance; Corporate governance; Insurance; Risk management; Economics; Management science